Openness Toward Organizational Change Scale (OTOCS): Validity evidence from Brazil and Portugal - Sinval, J.; Miller, V.; Marôco, J. (PLoS One, 2021)
Openness toward organizational change is central to employees’ responses to organiza- tions’ strategic actions. This study aims to assess the validity evidence of the Openness Toward Organizational Change Scale (OTOCS) by examining the internal structure of the measure (e.g., dimensionality, reliability, measurement invariance) and its relations with other variables such as quality of work life, burnout, job satisfaction, and work engagement. A cross-sectional study was conducted using total sample of 1,175 workers, with 565 work- ers from Portugal and 610 from Brazil. The data provided satisfactory validity evidence based on the internal structure: the expected dimensionality was confirmed, acceptable lev- els of reliability were found, and measurement invariance was achieved among countries and sex. The measure also demonstrated satisfactory validity evidence based on the rela- tions to other variables, being negatively associated with burnout and positively associated with work engagement, job satisfaction and quality of work. The OTOCS proved to be a rela- tively short self-report measure with satisfactory validity evidence to be used among Brazil- ian and Portuguese workers.